2020
DOI: 10.1029/2020jf005736
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Insights Into the Threshold of Motion in Alluvial Channels: Sediment Supply and Streambed State

Abstract: Multiple bed surface characteristics, including surface grain size distribution (GSD), grain protrusion and surface roughness, and development of coarse-grain clusters, respond to water and sediment supply in ways that generally enhance bed stability. As the sediment supply decreases, the gravel-bed surfaces coarsen and bed stability increases (Dietrich et al., 1989; Gessler, 1970; Nelson et al., 2009). This armoring (surface coarsening relative to the subsurface or the sediment supply) occurs when transport c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 72 publications
5
25
0
Order By: Relevance
“…Previous researchers (Haynes and Pender, 2007;Masteller and Finnegan, 2017) have suggested that an exponential function can be implemented to describe such a decrease of sediment transport rate under conditioning flow. Additional analysis is implemented in the Supplement to fit REF2 (15) and REF6 (15) (which have the longest duration of conditioning phase) against a two-parameter exponential function.…”
Section: Sediment Transportmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous researchers (Haynes and Pender, 2007;Masteller and Finnegan, 2017) have suggested that an exponential function can be implemented to describe such a decrease of sediment transport rate under conditioning flow. Additional analysis is implemented in the Supplement to fit REF2 (15) and REF6 (15) (which have the longest duration of conditioning phase) against a two-parameter exponential function.…”
Section: Sediment Transportmentioning
confidence: 99%
“…To further study such "memory" effects of antecedent flow on the sediment transport during a subsequent flood, a number of flume experiments and field surveys have been conducted in the past decade, and different terms have been proposed, including "stress history effect" (Monteith and Pender, 2005;Paphitis and Collins, 2005;Haynes and Pender, 2007;Ockelford and Haynes, 2013), "flood history effect" (Mao, 2018), and "flow history" (Masteller et al, 2019). The difference in the terminology could be partly due to the available data and the chosen approach in different research works.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations